Crossed Cerebellar Diaschisis: Three Case Reports Imaging Using a Tri-Modality PET/CT–MR System. Issue 2 (January 2016) - Han, Shuguang; Wang, Xiaopeng; Xu, Kai; Hu, Chunfeng
Abstract : Abstract: Crossed cerebellar diaschisis (CCD) describes a depression of oxidative metabolism glucose and blood flow in the cerebellum secondary to a supratentorial lesion in the contralateral cerebral hemisphere. PET/MR has the potential to become a powerful tool for demonstrating and imaging intracranial lesions .We herein report 3 cases of CCD imaging using a tri-modality PET/CT–MR set-up for investigating the value of adding MRI rather than CT to PET in clinical routine. We describe 3 patients with CCD and neurological symptoms in conjunction with abnormal cerebral fluorodeoxyglucose (FDG) positron emission tomography/computed tomography-magnetic resonance imaging (PET/CT–MR) manifestations including arterial spin-labeling (ASL) and T2-weighted images. In all, 18 FDG-PET/CT detected positive FDG uptake in supratentorial lesions, and hypometabolism with atrophy in the contralateral cerebellum. More than that, hybrid PET/MRI provided a more accurate anatomic localization and ASL indicated disruption of the cortico-ponto-cerebellar pathway. Using pathology or long-term clinical follow-up to confirm the PET and ASL findings, the supratentorial lesions of the 3 patients were respectively diagnosed with cerebral infarction, recurrent glioma, and metastasis. The reports emphasize the signiﬁcance of multimodality radiological examinations. Multimodality imaging contributes to proper diagnosis, management, and follow-up of supratentorial lesions with CCD.